Influence of self-produced CO2 on postharvest life of heat-treated strawberries - Vicente, Ariel Roberto (2003)
Strawberries cv. Selva (75 or 90% superficial red color) were packaged with films having different permeability properties, heat-treated in an air oven (45 8C, 3 h), stored at 0 8C for 0, 7 or 14 days and then transferred to 20 8C for 2 days. The percentage of CO2 in the package atmosphere and the effect of heat treatment on the following parameters were recorded: weight loss, external color, lightness, anthocyanin content, firmness, titratable acidity, pH, total sugar, total phenol and fruit decay. The application of heat treatment alone reduced fungal decay and delayed red color development and fruit softening. When the treatment was performed on fruit in films that allowed retention of part of CO2 produced during heating, the delay of fruit softening and color development and the reduction of decay were enhanced. The benefit for 90% red fruit was minimal and decay development was only delayed by 1 day. The results of this work indicate that the well-known benefits of heat treatment could be considerably improved by performing the treatment in the presence of low permeability films, with the aim of retaining the CO2 produced by the temporary increase in fruit respiration during the heating